Training on the Use of Mendeley Application to Support the Ability of Teachers in Creating Publication Manuscripts - Sahrul Saehana; Darsikin Darsikin; Amiruddin Hatibe; Delthawati Isti Ratnaningtyas (Universitas Lambung Mangkurat, 2024)
The Mendeley application is a supporting tool for writers creating manuscripts for publication. Teachers need publications to improve their career path, especially achieving credit scores for promotion to functional positions. This program aims to train teachers in using the Mendeley application to make it easier to create publication manuscripts. Training activities were carried out by presenting ten teachers from PGRI Palu City, Central Sulawesi and two trainers. At the first meeting on July 23 2022, the teachers' ability to use this application was identified, and it was found that almost all teachers needed to be proficient in using it. Training is then carried out using presentation, demonstration, practice and question-and-answer methods. Next, three trainers guided the participants to recognize and apply their obtained information. At the second meeting on July 26 2022, participants completed citations on the manuscript created using the Mendeley application. Assistance is provided by the service team in language that is easily understood by the participants and immediately produces output in the form of a script. This training activity was carried out over two meetings, and the results of the final evaluation showed that the participants who were initially unable to use the Mendeley application (pretest) were then able to use the Mendeley Program well (posttest). It is hoped that the implications of this activity will help participants prepare research results manuscripts to help collect credit.